Developing of discursive competence at English classes in the higher educational institution in polylingual education - Lapko, I.N.; Pariy, Т.V.; Shayhutdinova, М.V. (KSU Publ., 2011)
The article is devoted to the determination of the main stages of the technology of developing of discursive competence at English classes in polylingual education on a gradual transfer of the text into discursive activities through the use of complex tasks involving the combination of different types of activities and in result cognitive, developing and creative functions of academic texts are realized and the conditions for the acquisition general and individual information culture are created. The authors carried out the serious work on the determination of the functions of the feedback of the text and discourse activities in teaching English to the students at the university in polylingual education.
Жоғары оқу орнында көптілді топтардағы шетел тілінің сабақтарында дискурсивті құзыреттілікті қалыптастыру
Keywords: foreign language; education; innovation; communication; polylingual; discursive; competence; high school; activity